Brain Drain, Brain Circulation, and the African Diaspora in the United States. Issue 1 (2nd January 2019) - Chand, Masud
ABSTRACT: African immigrants are among the most educated immigrants in the United States. Their rising numbers and their highly educated background point to the importance of studying this growing phenomenon. The reasons for moving to the U.S. include pull factors such as better salaries, living conditions, and career opportunities, as well push factors, such as poor-quality institutions, lack of infrastructure, corruption, and nepotism in their countries of origin. African immigrants, because of their skills, resources, and networks, can help provide much needed human, social, and financial capital to their countries of origin. This paper investigates the immigration of people born in Africa to the U.S. It analyzes their backgrounds, the reasons for their move, and their activities in engaging with their countries of origin. It uses the theoretical lens of brain drain and brain circulation to analyze how these take place in the context of recent African immigration to the U.S. It proposes some ways in which African countries can best engage with their diasporas in the U.S. in a manner that is beneficial to all the three parties involved – the country of origin, the U.S., and the diaspora itself.